Language and Identity - Hoyt, Alexander D. (1996)
This paper discusses the symbolic function of language. Language plays an important role in the identification of groups. We use it to present ourselves as a member of one or more groups. At the same time, we recognize others as members of particular groups based upon their linguistic usage.
Projekt MZOS
ENG